Identification of Baihesi aluminous A-type granite: Magmatic response to the onset of Cretaceous extension in eastern Jiangnan Massif, South China - Hu, Bojie; Zhang, Da; Zhang, Xinming; Zhang, Zhihui; Wang, Sen; Hu, Jiaxiu (Frontiers in Earth Science, 2023)
The Cretaceous lithospheric extension in South China is very distinct, and expressed by systematic extension-related geological records which are concentrated in coastal terrane, Shi-hang Rift and Jiangnan Massif. The Cretaceous extension in coastal terrane and Shi-hang Rift began almost simultaneously during 145-140 Ma, while there is a lack of reliable magmatic indication for tectonic extension in Jiangnan Massif during 145-140 Ma. This paper reports a newly discovered Baihesi granite with a concordant age of 142.52 ± 0.57 Ma (MSWD = 1.2) on the southeast margin of the eastern Jiangnan Massif. The Baihesi granite is a monzogranite, and classified as peraluminous, high-K calc-alkaline series. The trace-element compositions are characterized by relatively flat rare earth element patterns, strong depletion of Eu, slightly enriched light-rare earth elements, enrichment of Cs, Rb, Th, U and Pb, and depletion of Ba, Sr, P and Ti. Combined with other petrochemistry characteristics, such as high SiO2 content, high differentiation index, low Zr/Hf and Nb/Ta ratios, low ratio between light- and heavy-REEs, low P2O5 content, and high zirconium saturation temperature, Baihesi granite is proved to be highly evolved aluminous A-type granite. The εHf(t) values of Baihesi granite range from −5.57 to −2.37 with two-stage model ages (TDM2) ranging from 1551 to 1345 Ma, suggesting a similar source to Neoproterozoic arc-related magmatic rocks in the Shuangqiaoshan Group. We argue that Baihesi granite has originated mainly from partial melting of a reworked juvenile crust related to Neoproterozoic arc-related magmatism in Jiangnan Massif, which was controlled by the subduction process along the South China active continental margin. Furthermore, we constrain the onset of Cretaceous extension in eastern Jiangnan Massif to be 145-140 Ma, and highlight the Early Cretaceous reactivation of northeastern Jiangxi fault zone and the structural inheritance in intraplate tectonics.